The Role of International Organizations in the Solution of the Palestinian Issue - T M Khalayla (RUDN Journal of Political Science, 2012)
In the article, the role of states of the World community and International organizations in the solution of the Palestinian question, and also efficiency and effectiveness offered to the solution of this problem, are also considered.